Comparison of ambulatory blood pressure-lowering effects of higher doses of different calcium antagonists in uncontrolled hypertension: the Calcium Antagonist Controlled-Release High-Dose Therapy in Uncontrolled Refractory Hypertensive Patients (CARILLON) Study. (3rd September 2017) - Mizuno, Hiroyuki; Hoshide, Satoshi; Tomitani, Naoko; Kario, Kazuomi
Abstract: Background: Data are sparse regarding ambulatory blood pressure (BP) reduction of up-titration from a standard dose to a high dose in both nifedipine controlled-release (CR) and amlodipine. This was a prospective, randomized, multicenter, open-label trial. Patients and methods: Fifty-one uncontrolled hypertensives medicated by two or more antihypertensive drugs including a renin-angiotensin system inhibitor and a calcium antagonist were randomly assigned to either the nifedipine CR (80 mg)/candesartan (8 mg) group or the amlodipine (10 mg)/candesartan (8 mg) group. Results: The changes in 24-hr BP were comparable between the groups. The nifedipine group demonstrated a significant decrease in their urinary albumin creatinine ratio, whereas the amlodipine group demonstrated a significant decrease in their NTproBNP level. However, there was no significant difference in any biomarkers between the two groups. Conclusion: Nifedipine showed an almost equal effect on ambulatory blood pressure as amlodipine. Their potentially differential effects on renal protection and NTproBNP should be tested in larger samples.